Calcium dobesilate may improve hemorheology in patients undergoing coronary artery bypass grafting - Besirli,Kazim (2012)
BACKGROUND: Calcium dobesilate is an angioprotective agent that has positive effects on hemorheological parameters. It is an antioxidant that increases endothelial-derived vasodilator substance secretion, there are none that analyze its effects during the postoperative period of patients undergoing myocardial revascularization. OBJECTIVE: We aimed to determine the effects of calcium dobesilate on hemorheological parameters, such as reduced glutathione and malondialdehyde in patients with ischemic heart disease undergoing myocardial revascularization in the postoperative period. METHODS: One hundred and thirty-four patients operated for coronary heart disease were included in this study. Hemorheological, oxidant and antioxidant parameters were measured two days after surgery and after a period of treatment with calcium dobesilate. Then, 500 mg of calcium dobesilate was given twice a day to one group of 68 patients for three months. The control group was composed of 66 patients who did not receive this medication. RESULTS: The increase in the erythrocyte deformability index was found to be significant compared with both the pretreatment values and with the 1st and 2nd values of the control group after calcium dobesilate administration, whereas there were no significant changes in blood viscosity, glutathione (GSH) or malondialdehyde (MDA) values after the calcium dobesilate administration. The same improvement in the CCS class was observed in patients regardless of they received the calcium dobesilate treatment. CONCLUSION: In the present investigation, the same improvement in the CCS class was observed in patients regardless of they received the calcium dobesilate treatment. Improvements with calcium dobesilate were statistically significant only in the increase in erythrocyte flexibility.